(2a-1)((4a)(4a)+2a+1)=

Simple and best practice solution for (2a-1)((4a)(4a)+2a+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2a-1)((4a)(4a)+2a+1)= equation:


Simplifying
(2a + -1)((4a)(4a) + 2a + 1) = 0

Reorder the terms:
(-1 + 2a)((4a)(4a) + 2a + 1) = 0

Remove parenthesis around (4a)
(-1 + 2a)(4a(4a) + 2a + 1) = 0

Remove parenthesis around (4a)
(-1 + 2a)(4a * 4a + 2a + 1) = 0

Reorder the terms for easier multiplication:
(-1 + 2a)(4 * 4a * a + 2a + 1) = 0

Multiply 4 * 4
(-1 + 2a)(16a * a + 2a + 1) = 0

Multiply a * a
(-1 + 2a)(16a2 + 2a + 1) = 0

Reorder the terms:
(-1 + 2a)(1 + 2a + 16a2) = 0

Multiply (-1 + 2a) * (1 + 2a + 16a2)
(-1(1 + 2a + 16a2) + 2a * (1 + 2a + 16a2)) = 0
((1 * -1 + 2a * -1 + 16a2 * -1) + 2a * (1 + 2a + 16a2)) = 0
((-1 + -2a + -16a2) + 2a * (1 + 2a + 16a2)) = 0
(-1 + -2a + -16a2 + (1 * 2a + 2a * 2a + 16a2 * 2a)) = 0
(-1 + -2a + -16a2 + (2a + 4a2 + 32a3)) = 0

Reorder the terms:
(-1 + -2a + 2a + -16a2 + 4a2 + 32a3) = 0

Combine like terms: -2a + 2a = 0
(-1 + 0 + -16a2 + 4a2 + 32a3) = 0
(-1 + -16a2 + 4a2 + 32a3) = 0

Combine like terms: -16a2 + 4a2 = -12a2
(-1 + -12a2 + 32a3) = 0

Solving
-1 + -12a2 + 32a3 = 0

Solving for variable 'a'.

The solution to this equation could not be determined.

See similar equations:

| 9(t-6)+6t=5(3t+2)-8 | | 0.25(10000)-0.04y=0.06(y+10000) | | -150=-5(-5b) | | -3y=6 | | 4(2y-1)-(2y)=6 | | x^2+9=8x | | (12y+5)(12y-5)= | | 2+2x+2=46 | | 5-5=16s-12s | | 3x(2x-1)=1 | | 42=-2x+6 | | (8p^3+3p^2-4)+(6p^3-3p+5)= | | 2(3x-8)=38 | | -16=-2a+7(5-7a) | | 6x-10=68 | | -77=7(-8x-3) | | y-4(2)=0 | | 8=-4(-8n-2) | | -3(-8-6b)=6 | | 61=-5(1-8v)-7v | | -6=-6(-7-8n) | | -60=3(-7x+8) | | 7(3r+6)=21 | | 60=6(6m-7)-6 | | -4(3n-4)=-56 | | -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) |

Equations solver categories